A fast method for the evaluation of the dynamic positioning capability in time domain in the early design stage - Lübcke, Adele; Augener, Philip Herbert; Falkenhorst, Arne (ASME, 2015)
Vessels equipped with a Dynamic Positioning (DP) system for station keeping have become quite common on the offshore market. The propulsion system of such ships has the capability to compensate the counteracting environmental forces caused by wind, waves and current. Since the DP capability is an important part of the specification, it is necessary to consider this aspect in the early ship design stage. For this purpose a procedure of a fast calculation method is developed by the authors to predict the limiting environmental conditions and the maximum deviation of the position and the course angle for a pre-established propulsion system.